Pancreatic Cancer and Thromboembolism in the Ambulatory Community - Kornreich, Davida A; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Pancreatic exocrine adenocarcinoma is one of the most common malignancies associated with thromboembolism. The authors summarize the two abstracts (#368 and #273) presented at the 2012 ASCO Gastrointestinal Cancers Symposium which were focused on pancreatic thrombosis in ambulatory patients. In addition, they discuss the risk of thrombosis associated with malignancy, chemotherapy, and erythropoietin stimulating agents and the management and implications thereof.